Frequency of Vitamin B12 Deficiency in patients of Pancytopenia - Muhammad Nayyab Tahir, Husnain Athar, Maheen Shahid, Raneesha Umer, Abrar Ul H Aq (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Vitamin B12 insufficiency is prevalent in developing nations. It often causes megaloblasticanemia, but it may also impact the other two cell lines, i.e. platelets and leukocytes (pancytopenia), and may be misdiagnosed as cancer or bone marrow failure. A therapeutic test may be performed, providing a prompt diagnosis and preventing a high death rate. Aim To find frequency of vitamin B12 deficiency in children having pancytopenia. Methodology: This cross sectional study was done at Children’s Hospital &The Institute of Child Health Lahore in 6 months. This study involved 242 children of 6 months to 14 years age of both genders admitted in Children Hospital Lahore and had pancytopenia on their CBC. Results: The age of the patients ranged from 6 months to 14 years with a mean of 6.4±2.8 years. There were 111(45.9%) male and 131 (54.9%) female patients with a male to female ratio of 1:1.2. A total of 6.2% patients were found to have B12 deficiency. Conclusion: It is concluded that, 6.2% of patients with pancytopenia had a deficiency of B12; thus, patients may be routinely evaluated for pancytopenia and its reasons, since many of them are entirely curable and others are managed. Keywords: Vitamin B12 deficiency, cobalamin, Pancytopenia, Megaloblastic